Investigating Dream Phenomena in Ayurveda for Women: Diagnostic and Therapeutic Insights into Tridosha Imbalances - Prachi,; Sudheer Arya,; Sapna Ratan Shah, (International Journal of Ayurveda and Pharma Research, 2024)
This paper explores the role of dream phenomena in Ayurveda, particularly focusing on women. It examines how dreams are interpreted in relation to the Tridosha system (Vata, Pitta, Kapha) and their implications for diagnosing and treating Dosha imbalances. By integrating Ayurvedic principles with modern understanding of dreams, the study aims to provide a comprehensive framework for utilizing dream analysis in Ayurvedic practice. The analysis of dream patterns associated with Dosha imbalances among 50 women revealed notable trends in the frequency of dream experiences tied to each Dosha. The data showed that Pitta was the most frequently associated Dosha, with a total frequency count of 77 occurrences, representing 42% of the total dream patterns observed. This was followed closely by Vata, which accounted for 76 occurrences, or 41% of the total. Kapha had the lowest frequency with 39 occurrences, constituting 17% of the total. These results indicate that dream patterns reflecting fiery, intense, and chaotic elements were predominantly linked with Pitta imbalances, while disorganized and fragmented dreams were more commonly associated with Vata. Kapha imbalances, characterized by heavy and stagnant dream themes, were less frequent. The data suggests a significant correlation between specific dream phenomena and Dosha imbalances, highlighting the potential of dream analysis as a valuable diagnostic and therapeutic tool in Ayurvedic practice for understanding and addressing Dosha-related health issues in women.